Light Confinement Effect Induced Highly Sensitive, Self‐Driven Near‐Infrared Photodetector and Image Sensor Based on Multilayer PdSe2/Pyramid Si Heterojunction - Liang, Feng‐Xia; Zhao, Xing‐Yuan; Jiang, Jing‐Jing; Hu, Ji‐Gang; Xie, Wei‐Qiang; Lv, Jun; Zhang, Zhi‐Xiang; Wu, Di; Luo, Lin‐Bao (Small (Weinheim an der Bergstrasse, Germany), 2019)
In this study, a highly sensitive and self‐driven near‐infrared (NIR) light photodetector based on PdSe2/pyramid Si heterojunction arrays, which are fabricated through simple selenization of predeposited Pd nanofilm on black Si, is demonstrated. The as‐fabricated hybrid device exhibits excellent photoresponse performance in terms of a large on/off ratio of 1.6 × 105, a responsivity of 456 mA W−1, and a high specific detectivity of up to 9.97 × 1013 Jones under 980 nm illumination at zero bias. Such a relatively high sensitivity can be ascribed to the light trapping effect of the pyramid microstructure, which is confirmed by numerical modeling based on finite‐difference time domain. On the other hand, thanks to the broad optical absorption properties of PdSe2, the as‐fabricated device also exhibits obvious sensitivity to other NIR illuminations with wavelengths of 1300, 1550, and 1650 nm, which is beyond the photoresponse range of Si‐based devices. It is also found that the PdSe2/pyramid Si heterojunction device can also function as an NIR light sensor, which can readily record both “tree” and “house” images produced by 980 and 1300 nm illumination, respectively. A highly sensitive near‐infrared light photodetector based on PdSe2/pyramid Si heterojunction arrays is developed. The as‐fabricated hybrid device exhibits excellent photoresponse performance in terms of a large on/off ratio of 1.6 × 105, a responsivity of 456 mA W−1, and a high specific detectivity of up to 9.97 × 1013 Jones under 980 nm illumination at zero bias.